POTENTIAL OF GARLIC EXTRACT (Allium sativum L.) TO THE GROWTH OF Colletotrichum acutatum FUNGUS WHICH CAUSE ROT OF RED CHILI FRUIT (Capsicumum acutatum Fungus Which Cause Rot of Red Chili Fruit (Capsicum annuum L.) Post Harvest - Agustini, Fania; Darmayasa, Ida Bagus Gede; Arpiwi, Ni Luh (SIMBIOSIS, 2022)
This study aims to find out the potency of garlic extract (Allium sativum L.) to the growth of Colletotrichum acutatum fungus which cause rot of red chili fruit post-harvest. The treatments were the administration of garlic extract in-vitro and in-vivo. In the in-vitro test, the inhibition of garlic extract was measured using well diffusion method. The in-vivo test was conducted by measuring the diameter area of C. acutatum on red chilies after treatments. The concentration of garlic extract given was 15%(b/v), 20%(b/v), 25%(b/v), 30%(b/v), and 35%(b/v) with positive control of synthetic fungicides and negative control of ethanol solvents 95% and 4 times replications. The average diameter result on the 25%(b/v) concentration of bland power test had the most effective bland zone diameter of 20.1±0.08. Statistically different was real (P?0.05) with negative controls. While in vivo tests the average area of infection area at a concentration of 35%(b/v) had an average diameter area of infection area which was best in inhibiting the growth of C. acutatum fungus.